Organizational Compliance During COVID-19: Investigating the Effects of Anxiety, Productivity, and Individual Risk Factors Among Iranian Healthcare Employees - Rahmani, Diyako; Zeng, Cheng; Goodarzi, Ali Moazami; Vahid, Farhad (Frontiers in Communication, 2021)
This study investigates the impact of anxiety, productivity, and individual characteristics on employee compliance in an Iranian medical science university during the COVID-19 outbreak. The data of 160 healthcare employees of various professions were collected with reliability and validity on the measurements performed. Two regression tests revealed that higher anxiety reduces and higher productivity increased compliance. Participants with higher education and non-medical professions were found to have higher compliance. Productivity was also found to be positively associated with tenure and having a medical position. Implication and limitation are discussed.